High‐productivity vegetation is important for lessening bird declines during prolonged drought. Issue 2 (28th December 2017) - Selwood, Katherine E.; McGeoch, Melodie A.; Clarke, Rohan H.; Mac Nally, Ralph
Abstract: Locations in which ecological assemblages show high resistance to climate pressures, such as drought, are likely to be important refuges for biota in changing climates. We asked whether environmental characteristics of locations were associated with the capacity of bird assemblages to withstand prolonged drought. We used a multispecies index to quantify trends in bird assemblages during a 13‐year drought at >500 locations (>18, 000 surveys) in the Murray–Darling Basin, south‐eastern Australia, using data from the Atlas of Australian Birds. We investigated whether the resistance of bird assemblages was associated with (1) vegetation structure; (2) vegetation productivity (vegetation greenness); (3) landscape context (patch size, landscape vegetation cover); or (4) physical environment (elevation, terrain, topography, availability of surface water). Vegetation productivity, measured by vegetation greenness (Normalized Difference Vegetation Index), was the only potential predictor with strong evidence of an effect, and was positively associated with the index of drought resistance. There was little evidence that variables characterizing landscape context, vegetation structure or the physical environment of sites were associated with drought resistance of bird communities. Synthesis and applications . Bird assemblages in locations with high vegetation greenness are more resistant to severe drought. Prioritizing conservation investments in areas with locally high vegetation productivity is likely to be an effective strategy for increasing the resistance of bird assemblages to extreme drought, especially in areas where mean productivity is relatively low, such as arid and semi‐arid regions. Remotely sensed vegetation greenness may be a promising source of information for identifying drought refuges for birds and possibly other biota. Abstract : Bird assemblages in locations with high vegetation greenness are more resistant to severe drought. Prioritizing conservation investments in areas with locally high vegetation productivity is likely to be an effective strategy for increasing the resistance of bird assemblages to extreme drought, especially in areas where mean productivity is relatively low, such as arid and semi‐arid regions. Remotely sensed vegetation greenness may be a promising source of information for identifying drought refuges for birds and possibly other biota.